Family educational patterns in strengthening teenager's character generation z: A literature review - Fransiskus Markus Pereto Keraf; Marsianus Falo; Ody Wolfrit Matoneng; Fredik Lambertus Kollo Kollo; Nurlailah Nurlailah (Inovasi Kurikulum, 2024)
Generation Z teenagers were born in the internet and technological automation era. The negative impact of technological developments causes violations of applicable norms. Teenagers who are involved in juvenile delinquency are caused by a lack of assistance and family control. This study aims to identify appropriate educational patterns for integrating positive moral habits and norms in the family. The writing method uses a literature review. The data collection process through a literature review is supported by a comprehensive analysis of publications from academic journals in the last 5 (five) years, focusing on educational patterns in the family to strengthen the character of Generation Z teenagers. The study results show that there are 3 (three) patterns of education in the family to develop the character of Generation Z teenagers. The three education patterns are family education patterns based on example, monitoring, and understanding psychology. Parents must integrate these three educational patterns in the family to create a golden generation with positive, quality characters. Character development formed through family educational patterns can be collaborated with other character education models, such as in the school or community environment.   Abstrak Remaja generasi Z lahir di era internet serta otomatisasi teknologi. Dampak negatif perkembangan teknologi menyebabkan terjadinya pelangaran norma yang berlaku. Remaja yang terlibat kenakalan remaja disebabkan kurangnya pendampingan serta kontrol keluarga. Kajian ini bertujuan mengidentifikasi pola pendidikan yang tepat dalam mengintegrasikan pembiasaan moral dan norma yang positif dalam keluarga. Adapun metode penulisan menggunakan kajian pustaka. Proses pengumpulan data melalui tinjauan literatur ini didukung oleh analisis publikasi yang komprehensif dari jurnal akademik pada 5 (lima) tahun terakhir, berfokus pada pola pendidikan dalam keluarga untuk menguatkan karakter remaja generasi z. Hasil kajian menunjukan bahwa terdapat 3 (tiga) pola pendidikan dalam keluarga untuk mengembangkan karakter remaja generasi z. Ketiga pola pendidikan tersebut yakni pola pendidikan keluarga melalui keteladanan, pemantauan dan pemahaman psikologi. Orangtua harus mampu mengintegrasikan ketiga pola pendidikan dalam keluarga tersebut untuk mewujudkan generasi emas yang memiliki karakter positif berkualitas. Pengembangan karakter yang dibentuk melalui pola pendidikan dalam keluarga dapat dikolaborasikan dengan model pendidikan karakter lainnya, seperti di lingkungan sekolah maupun masyarakat. Kata Kunci: generasi z; karakter remaja; pendidikan keluarga